Who is telling the story? A systematic review of authorship for infectious disease research conducted in Africa, 1980–2016 - Stefanie Hossmann; Yap Boum; Rose Mbaye; Redeat Gebeyehu; Nicole Mbarga; Estella Bih-Neh; Lucrece Eteki; Ohene-Agyei Thelma; Abiodun Oyerinde; Gift Kiti; Yvonne Mburu; Jessica Haberer; et al. (BMJ Global Health)
Introduction Africa contributes little to the biomedical literature despite its high burden of infectious diseases. Global health research partnerships aimed at addressing Africa-endemic disease may be polarised. Therefore, we assessed the contribution of researchers in Africa to research on six infectious diseases.Methods We reviewed publications on HIV and malaria (2013–2016), tuberculosis (2014–2016), salmonellosis, Ebola haemorrhagic fever and Buruli ulcer disease (1980–2016) conducted in Africa and indexed in the PubMed database using Preferred Reporting Items for Systematic Reviews and Meta-Analyses protocol. Papers reporting original research done in Africa with at least one laboratory test performed on biological samples were included. We studied African author proportion and placement per study type, disease, funding, study country and lingua franca.Results We included 1182 of 2871 retrieved articles that met the inclusion criteria. Of these, 1109 (93.2%) had at least one Africa-based author, 552 (49.8%) had an African first author and 41.3% (n=458) an African last author. Papers on salmonellosis and tuberculosis had a higher proportion of African last authors (p<0.001) compared with the other diseases. Most of African first and last authors had an affiliation from an Anglophone country. HIV, malaria, tuberculosis and Ebola had the most extramurally funded studies (≥70%), but less than 10% of the acknowledged funding was from an African funder.Conclusion African researchers are under-represented in first and last authorship positions in papers published from research done in Africa. This calls for greater investment in capacity building and equitable research partnerships at every level of the global health community.